Barriers to and Incentives for Safety Event Reporting in Emergency Departments - Jeffrey R Brubacher, Garth S Hunte, Lynsey Hamilton and Annemarie Taylor (Healthcare Quarterly, 2011)
Patient safety events (PSEs) are common in healthcare and may be particularly prevalent in complex care settings such as emergency departments (EDs). Systems for reporting, analyzing, learning from and responding to incidents are promoted as a means to reduce adverse events by facilitating feedback, learning and system change. However, only 4–50% of PSEs are reported. Under-reporting masks the true number of PSEs and may reduce our ability to learn from and prevent repeat events. The goal of this study was to identify barriers that prevent PSE reporting and incentives that encourage reporting.
Keywords: Jeffery Brubacher, Garth Hunte, Lynsey Hamilton, Annemarie Taylor, patient safety, emergency department, incident reporting